Cultivating Scientific Literacy and Self-confidence through an Islamic-Oriented 9E Learning Cycle in Biology Education - Bidayati Haka, Nukhbatul; Satiyo Putri, Bella; Hidayah, Nur; Rakhmawati, Ismi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study evaluates the Islam-oriented 9E Learning Cycle for enhancing scientific literacy and self-confidence in secondary school biology. Using a quasi-experimental pretest–posttest control-group design, two Grade X classes participated: the experimental class learned via the 9E model infused with Islamic values, while the control class received discovery learning. Data were collected through PISA aligned literacy tests and questionnaires, validated self-confidence scales, and observation sheets, all demonstrating reliability (Cronbach’s α > .70). Independent t-tests and correlation analyses showed that the experimental group achieved higher posttest scores and larger normalized gains in scientific literacy (N-gain = 0.70, high) and self-confidence (N-gain = 0.69, moderate). Explained-variance estimates indicated contributions of 17.3% to literacy and 14.8% to self-confidence. Findings suggest that integrating spiritual ethical dimensions within a structured inquiry cycle strengthens conceptual mastery and nurtures affective development, positioning the Islam oriented 9E model as a holistic pedagogical strategy for curriculum reform and teacher professional development in faith-based contexts. Menumbuhkan Literasi Sains dan Rasa Percaya Diri melalui Siklus Pembelajaran 9E Berorientasi Islam dalam Pendidikan Biologi ABSTRAK: Penelitian ini mengevaluasi efektivitas Learning Cycle 9E berorientasi Islam dalam meningkatkan literasi sains dan kepercayaan diri pada pembelajaran biologi di sekolah menengah. Dengan desain kuasi-eksperimental pretest–postest control grup design, kelas eksperimen belajar melalui model 9E yang orientasi nilai-nilai Islam, sedangkan kelas kontrol menggunakan discovery learning. Data dikumpulkan melalui tes dan kuesioner literasi sains framwork PISA 2025, skala kepercayaan diri tervalidasi, serta lembar observasi; seluruh instrumen menunjukkan reliabilitas baik (Cronbach’s α > .70). Uji t independen dan analisis korelasi menunjukkan kelas eksperimen meraih skor pascates lebih tinggi dan gain ternormalisasi lebih besar pada literasi sains (N-gain = 0,70; tinggi) dan kepercayaan diri (N-gain = 0,69; sedang). Estimasi variasi yang dijelaskan mengindikasikan kontribusi 17,3% terhadap literasi dan 14,8% terhadap kepercayaan diri. Temuan ini menyiratkan bahwa integrasi dimensi spiritual etis dalam siklus inkuiri terstruktur memperkuat penguasaan konseptual sekaligus menumbuhkan aspek afektif, sehingga model 9E berorientasi Islam layak diposisikan sebagai strategi pedagogis holistik bagi reformasi kurikulum dan pengembangan profesional guru di konteks pendidikan berbasis keagamaan.